Pengaruh Model Pembelajaran Problem Based Learning Berbantuan Media Animasi Terhadap Minat dan Hasil Belajar Siswa - Tri Wulandari; Rohimin Rohimin; Nurlaili Nurlaili; Gusti Rian Saputra (Lembaga Sosial Rumah Indonesia, 2023)
Using appropriate learning models is important in education. However, sometimes this aspect is often forgotten. So that it gives the impression that education practitioners are only